A drama of selves: Investigating teacher identity development from dialogical and complexity perspectives - Henry, Alastair (Studies in Second Language Learning and Teaching, 2019)
Identity is of increasing interest in teacher education. Crucial for resilience, the development of a coherent professional identity has been characterized as emerging from tensions between multiple and sometimes conflicting conceptions of what it means to be someone who teaches (Akkerman & Meijer, 2011). While light is being shed on these often antagonistic relations, less is known about the dynamics of identity formation and transformation. Providing a contribution to work on language teacher identity, in this single case study Hermans’ (2008) concept of the dialogical self is combined with complexity principles in an investigation of changes in the emerging professional identity of a pre-service English teacher during a practicum. Drawing on intra- and inter-personal data, experiences of learning to become a person who teaches English are conceptualized as a drama that is played out between different and sometimes unaligned selves. Analyses show how this inner drama maps onto the landscape of an emerging teacher identity, how tensions can be understood systemically, and how a teacher identity system can have a signature dynamic.